Iron Daggers and Swords in the Yayoi Period - Ege, Kazuhiro (Nihon Kokogaku(Journal of the Japanese Archaeological Association), 2007)
Iron daggers and swords in the Yayoi period varied in size and style, and they were distributed rather irregularly in each phase in the Japanese Archipelago. In this article, iron daggers and swords of the Yayoi period were compared with those of the southern Korean Peninsula, for which archaeological data has increased, and thoughts were given on their meaning by examining aspects of production, distribution, and consumption as funerary equipment. First was examination of the hypothesis that among the daggers from middle to the final stage of Late Yayoi in the Japanese Archipelago, long daggers with long and narrow handles were imported, and short daggers contained some that were made in Japan. As for distribution, many long daggers with long and narrow handles and iron swords were distributed on the Sea of Japan side of Honshu, and this area overlapped with the distribution of large burial pits and glass cylindrical beads used for funerary equipment. Many of the long daggers distributed in eastern Japan had short handles and a flat trapezoidal shape. This regional difference suggests a strong reflection of consumer demands in the distribution process through transit trade. On the aspects of consumption in funerary equipment of mound tombs, most individuals buried with funerary equipment in the coffin were adult males. Some mound tombs in the final phase of the Yayoi period saw juveniles buried with funerary equipment, but this was unusual. Also, thoughts were given on a possibility that the awareness of "hekija"existed as one of the basic philosophies underlying burying iron daggers and swords, although some verification research is necessary in the future. Many of the tombs with large burial pits had iron daggers and swords buried in them, and among those, some contained imported long daggers and large swords, but on the other hand, some had short daggers and only tips of sword blades. As for the background for distribution of long daggers and iron swords through the Sea of Japan that were used as funerary equipment among some of the upper class tombs of the Japanese Archipelago and southern Korean Peninsula, it can be pointed out that information on social circumstances in regions around the Sea of Japan and" political" relations between the groups were some of conditions attached to the products. One necessary research topic in the future is to conduct comparative examination on the usage of weapons for close combat or weapon-shaped products in different regions, and their historical connection and meaning as the background, including those other than iron daggers and swords, such as stone weapons and weapon-shaped bronze objects.